The Dhammadesana Strategy of Buddhist Puppet Ki Eko Prasetyo - Rapiadi Rapiadi; Joko Santoso; Wistina Seneru; Lamirin Lamirin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This paper discusses the strategy of implementing Dhammadesana or lectures in Buddhism using wayang media presented by Ki Eko Prasetyo. Wayang as one of the objects and performances of cultural arts in several regions in Indonesia such as in Java and Bali has become a distinctive identity that cannot be separated from Indonesia. The use of this puppet in spreading religious teachings has been used as an alternative chosen by various groups, one of which is what was done by Ki Eko Prasetyo as one of the figures who spread religious teachings through wayang media and uploaded to social media Youtube. The research method used is qualitative research using virtual ethnography. The data used is primary data from Ki Eko Prasetyo's puppet show on Youtube and secondary data that supports the discussion comes from literary sources. The results of this paper indicate that as a strategy in delivering Dhamma to Buddhists, the wayang Ki Eko Prasetyo can be a solution that is able to accommodate Dhamma messages. But of course, the delivery of the Dhamma message from Ki Eko Prasetyo's wayang performance needs to always be considered by Buddhists when receiving the Dhamma message. The use of words in the performance must be clearly chosen in order to avoid misinterpretation of the audience of the Ki Eko Prasetyo puppet show.